Effectiveness of a Community-Based Physical Activity and Nutrition Behavior Intervention on Features of the Metabolic Syndrome: A Cluster-Randomized Controlled Trial. - Tran, V.; James, Tony; Lee, Andy; Jancey, Jonine; Howat, Peter; Thi Phuong Mai, L. (2017)
Background: Metabolic syndrome (MetS) and its subclinical diseases are now public health problems in Vietnam. This study aimed at determining the effectiveness of a physical activity and nutrition program for reducing MetS proportion and its components among adults with MetS in Hanam province, Vietnam. Methods: A total of 417 volunteers aged 50–65 years with MetS were recruited from 10 communes. The communes were randomly allocated to an intervention group (five communes, n = 214) and a control group (five communes, n = 203). The participants in the intervention group received a nutrition and physical activity program for 6 months, whereas participants in the control group received standard diet and physical activity advice on only one occasion. Anthropometry, lipid profiles, glycemic status, and blood pressure were measured at baseline and at 6 months to evaluate program effectiveness. Results: In total, 175 intervention (81.8%) and 162 control (79.8%) participants completed the post-program evaluation. After controlling for the effects of clustering and confounding factors, the intervention group showed significant improvements in high-density lipoprotein cholesterol (+0.42 mM, P < 0.001), waist circumference (−1.63 cm, P < 0.001), waist-to-hip ratio (−0.024, P < 0.001), weight (−1.44 kg, P < 0.001), and body mass index (−0.59 kg/m2, P < 0.001) when compared with the control group. A reduction in the MetS proportion was found in both intervention and control groups (P < 0.001), decreasing to 56.0% and 75.9%, respectively, but the post-program proportion was significantly lower among the intervention participants (P < 0.001). Furthermore, the mean number of MetS components exhibited by individuals decreased significantly in the intervention group (P < 0.001). Conclusions: The community-based physical activity and nutrition program reduced MetS proportion, with significant improvements in several metabolic and anthropometric parameters for Vietnamese adults with MetS.